EFEKTIVITAS LOGOTERAPI DALAM MENINGKATKAN KEBERMAKNAAN HIDUP PADA NARAPIDANA - Ahmad, Mutia aini; Subandi, Subandi (UIN Sunan Kalijaga Yogyakarta, 2022)
This study aims to see the effectiveness of logotherapy in increasing the meaning of life in prisoners. People who commit crimes are people who have lost their meaning, they feel a false existential. Being in prison is an unpleasant experience, but when painful things cannot be interpreted, a person will not find his true self. In this study using the experimental method with a one group pretest posttest design. Logotherapy was given to 6 prisoners who were selected based on certain criteria. The intervention lasted 90-120 minutes per session, totaling 6 sessions. This study uses a non-parametric statistical analysis test with Wilcoxon sign-rank. The results of the significance scale scores were analyzed using the Wilcoxon sign-rank test. Based on the results of the different test on the significance scale score above, the p value was 0.046 (p < 0.05). Based on these results, it can be concluded that there is a significant difference in the meaning of inmates' lives before and after being given logotherapy. Keywords: Logotherapy, the meaning of life, prisoners